If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -91 = 7p Solving -91 = 7p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7p' to each side of the equation. -91 + -7p = 7p + -7p Combine like terms: 7p + -7p = 0 -91 + -7p = 0 Add '91' to each side of the equation. -91 + 91 + -7p = 0 + 91 Combine like terms: -91 + 91 = 0 0 + -7p = 0 + 91 -7p = 0 + 91 Combine like terms: 0 + 91 = 91 -7p = 91 Divide each side by '-7'. p = -13 Simplifying p = -13
| 2a-1=-(a+4) | | 24+9n=-3 | | 12x^2=18x-1 | | 5(m+3)+7m=3(m-9) | | 5(-7x+2)=-40 | | 3(3n+40)=54+6n | | 24=8c | | -3x-15=9x+9 | | m+4=1 | | 2x^2+3-5=0 | | 6p=-96 | | n/8=-12 | | 30=12n-18 | | -5+n=-23 | | -632=4g | | -9j-10=62 | | 8=-12+x | | 2=4h-14 | | 5w-3w= | | -6=v-4 | | 6x+8=2x-28 | | 18+5.50x=y | | J+434=-376 | | (-4x-5)=-125 | | Y=(x^2+5)2x+1 | | 2x^2+5x+15=0 | | 49=16+3j | | -10=x-17 | | -7-5(8n*8)=193 | | 6=d/7 | | -2x=-26 | | 4x^2+3x-76=0 |